Thematic Variety in Fiction of A Khayyam - kousar, Humaira; Night, Tayyaba (sourcecoder, 2024)
A Khayyam is first of all a dervish writer of fiction who keeps close eye on the environment. Also analyzes incidents and accidents. A Khayyam is a multi-faceted literary personality; he has left deep impressions of his art on many genres of Urdu literature. As an authentic fiction writer, novelist, essayist, and columnist, he has acknowledged his creativity in the world of literature. A Khayyam takes the themes of his fictions from life and the problems faced in it. His fictional collections "kapil Vastu ka shahzada ", Khali Haat, Jannat Jahannam and other fictions deserve to be called the assets of the overall tradition of Urdu fiction. The subject of his is "life". He has been awarded national and international honors in recognition of literary services. A. Khayyam has written on many topics related to history, psychology, social and economic conditions. In this research article, thematic variety in fiction of A Khayyam will be presented.